IMPLEMENTASI KONSELING INDIVIDU DALAM MENGURANGI KECEMASAN DAN MASALAH EMOSIONAL ANAK BINAAN DI LPKA KELAS I TANGGERANG - Putri, Deswinta Amanda; Warih Handoyo, Alfiiandy; Nurmala, Meilla Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Juvenile inmates at the Juvenile Correctional Institution (Lembaga Pembinaan Khusus Anak/LPKA) constitute a group of adolescents who are in a developmental stage that is highly vulnerable to various psychological problems, particularly anxiety and emotional disturbances. This vulnerability is influenced by limited freedom, separation from family, sudden changes in the social environment, and social stigma associated with being juvenile inmates. These conditions often lead to psychological pressure that results in emotional instability, fear, excessive anxiety, and difficulties in managing negative emotions during the rehabilitation period. Therefore, appropriate and continuous interventions through psychological services that are tailored to the individual needs of juvenile inmates are necessary. One service considered effective in addressing these problems is individual counseling. Individual counseling provides a safe and supportive space for juvenile inmates to express their feelings, disclose personal issues, and reflect on their experiences without fear of negative judgment. Through the individual counseling process, counselors assist juvenile inmates in understanding the sources of their anxiety and emotional problems and in developing more adaptive emotional regulation strategies. This study aims to provide an in-depth description of the implementation of individual counseling as an effort to reduce anxiety levels and address emotional problems among juvenile inmates at LPKA. The study employs a qualitative approach with a case study design. Data collection techniques include counseling interviews, observation, and documentation. The results indicate that individual counseling plays a significant role in enhancing emotional awareness, reducing anxiety, and strengthening self-acceptance among juvenile inmates. This service also helps prepare the psychological condition of juvenile inmates to face the rehabilitation period and their post-release life. Overall, these findings support the strengthening of systematic, continuous, and rehabilitative-oriented individual counseling services within the LPKA environment.